Integration analysis identifies the role of metallothionein in the progression from hepatic steatosis to steatohepatitis - Li, Xiaoya; Zhong, Shaoping; Sun, Yifan; Huang, Xinmei; Li, Yue; Wang, Lihong; Wu, Yueyue; Yang, Min; Yuan, Hai-Xin; Liu, Jun; Zang, Shufei (Frontiers in Endocrinology, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD), a metabolic disorder that develops from non-alcoholic fatty liver (NAFL) to non-alcoholic steatohepatitis (NASH), has become an epidemic chronic liver dysfunction worldwide. However, mechanisms that govern the transition from NAFL to NASH have not been fully elucidated. Methods: Gene expression profile data of NAFLD liver tissues were obtained from Gene Expression Omnibus (GEO), including three microarray datasets with 60 NAFL and 44 NASH patients. Integrative differentially expressed genes (DEGs) between NAFL and NASH patients were identified using robust rank aggregation (RRA) analysis. Hub genes were identified combined with gene ontology functional annotation, protein-protein interaction network construction and validated using a sequencing dataset. Huh-7 cells with palmitate-induced lipid-overload and NAFLD-diet mouse model of different stages were used to verified our findings. Results: RRA analysis determined 70 robust DEGs between NAFL and NASH. The most robustly upregulated genes were SPP1, AKR1B10, CHST9 and ANXA2, while the most robustly downregulated DEGs were SNORD94, SCARNA10, SNORA20 and MT1M. Cellular response to zinc ion (GO: 0071294) ranked first in GO analysis of downregulated genes, and KEGG enrichment showed that mineral absorption (hsa04978) was significantly enriched. The involvement of metallothionein pathway was further validated by the decrease of Mt1 expression during NAFL to NASH progression in NAFLD mice and the protection from lipotoxicity in liver cells by overexpressing MT1M. Conclusions: Our integrated analysis identified novel gene signatures and provided comprehensive molecular mechanisms underlying the transition from NAFL to NASH. Metallothionein might be a potential intervention target for NAFLD progression.